Arrangement and three-dimensional analysis of cooling wall in 1000 MW S–CO2 coal-fired boiler. (15th April 2020) - Yang, D.L.; Tang, G.H.; Fan, Y.H.; Li, X.L.; Wang, S.Q.
Abstract: The Supercritical carbon dioxide (S–CO2 ) Brayton cycle is considered as a promising alternative to traditional steam Rankine cycle due to its high efficiency and compactness. However, in coal-fired power system, the S–CO2 temperature at cooling wall entrance is newly recognized quite high, leading to an over-temperature crisis. A coupled model of combustion and S–CO2 heat transfer was established to predict cooling wall temperature of a 1000 MW S–CO2 Brayton coal-fired boiler. Based on the module arrangement in S–CO2 boiler, the "cold S–CO2 -hot fire matching and cascaded temperature control" principle in 1D model was proposed to reduce the cooling wall temperature. Three methods were examined including the low-temperature fluid matching high heat flux burner region, the counterflow, and more cold fluid in circulation drained to match high heat flux zone. The results show that the optimal arrangement can significantly reduce the temperature in overheated region 12–44 °C and eliminate the local hot spot. In addition, the 3D model was developed to obtain the maximum wall temperature and the uneven temperature in the circumferential direction. The employment of spiral cooling wall could alleviate circumferential unevenness and reduce wall temperature. The present work can provide important guidance to design of S–CO2 Brayton coal-fired power system. Highlights: A coupled model of combustion and S–CO2 heat transfer was established to predict cooling wall temperature. The "cold S–CO2 -hot fire matching and cascaded temperature control" principle in 1D model was proposed. The uneven temperature distribution in circumferential direction of cooling wall in 3D model was calculated. The spiral tubes of cooling wall could effectively relieve uneven problem and reduce wall temperature.